Guía de diagnóstico y autoevaluación del nivel de madurez del sistema de gestión en pymes con fines de implementación de acciones para el logro del éxito sostenido. (2020)
Carlos Andriani et al (2003) affirm that SMEs constitute in any country the predominant group of companies that in some cases exceed 99% of economic units, Viloria (2011) therefore small and medium-sized companies in Colombia have begun to worry Due to the need to carry out good business management, contributing to this, the objective of this degree project was to develop a guide for the interpretation, diagnosis, self-evaluation of maturity and implementation of actions to improve the management system applicable in small companies based on the guide. ISO 9004: 2018 technique. For this achievement, we started with establishing an initial structure of the guide based on the information identified pertinent to the development of said guide, generating the initial structure which was shared with three validators who are experts in management systems along with a qualification format of the guide so that they will participate validating the clarity of the content of the guide, after this important result, pertinent adjustments were found to apply according to the comments of the validators, which were applied complementing the final result of the degree project.